Concomitant ileocecal intussusception due to cecal lipoma and paraduodenal hernia - Thomas A. O'Hara; Maeghan L. Ciampa; Constance L. Joel; Kay E. Bush; Robyn M. Hatley (Elsevier, 2022)
We present a healthy adolescent male with no past surgical history who presented with acute onset abdominal pain. Cross-sectional imaging was concerning for possible ileocecal intussusception, and repeat imaging demonstrated an internal hernia. The patient was taken to the operating room for exploration. He was discovered to have an ileocecal intussusception with a large cecal mass, as well as a left paraduodenal hernia. Closure of the mesenteric defect and ileocecectomy with primary anastomosis were performed. Pathology of the mass was consistent with colonic lipoma. Postoperatively, he had slow return of bowel function, but his recovery was otherwise uncomplicated. This case reports a rare presentation of concomitant ileocecal intussusception due to a cecal lipoma and congenital internal hernia. Intussusception in the pediatric population is typically idiopathic, and intussusception with a pathologic lead point is far more common in adults. Gastrointestinal lipomas are also uncommon in pediatric patients, and when discovered are generally small and asymptomatic. Internal hernias most commonly are due to acquired mesenteric defects or adhesive disease, though may present congenitally as seen in this patient. This case is unique because of the simultaneous occurrence of two separate surgical problems, both with atypical etiologies based on patient history and demographics.